Pemberdayaan Masyarakat Petani dalam Pengelolaan Pupuk dan Pestisida Organik dari Tanaman Lokal di Desa Wolofeo Kecamatan Detusoko Kabupaten Ende - Yustina Maria Silvia Wonga Puu; Agustinus J.P. Ana Saga; Baltasar Taruma Djata; Charly Mutiara (PRIMA: Journal of Community Empowering and Services, 2019)
Title: Farmer Community Empowerment in Organic Fertilizers and Pesticides Management from Local Plants in Wolofeo Village, Detusoko District, Ende Regency. The Community in Wolofeo Village, Ende Regency do not yet know the process of organically cultivating plants. Also, they are very dependent on organic fertilizers and pesticides. The purpose of this service is to empower farmers to understand about organic farming and be able to make and use organic fertilizers and pesticides. This activity was carried out for one month, involving 20 students from the University of Flores and 50 farmers. The method used is counseling and training. Counseling has done that is about organic farming and integrated pest and disease control. And training was making organic fertilizers and pesticides and yellow traps. The results of the activities showed that there was an increase in community knowledge of 23.18% and skills of 27.46%.